Maskulinitas Crossdresser Laki-Laki Dalam Dunia Dance Cover K-Pop - Suganda, Vellania; Primadini, Intan (School of Communication Science and Media Business, 2024)
This research discusses how popular culture is growing in Indonesia. One of them is the K-pop culture originating from South Korea which is among Indonesian teenagers. Indonesian youth's interest in K-pop encourages their creativity and makes it easier for them to express themselves, giving rise to the trend of K-pop dance covers. Individuals imitate the dress styles, hairstyles, makeup, and accessories of their idols. Individuals are allowed to perform male to female cross-gender dance and vice versa. This activity eventually led to conflict related to Indonesian culture which sees men as having a masculine appearance and character. Therefore, this study aims to reveal how male crossdressers in K-pop dance covers interpret masculinity. This study uses a qualitative approach, Smith's interpretive phenomenology method, and the constructivism paradigm. The results showed that male crossdressers see masculinity as a form of behavior, not only in terms of physical appearance. Keywords: K-Pop, crossdresser, dance cover, idol, masculinity